2018
DOI: 10.1002/ajcp.12248
|View full text |Cite
|
Sign up to set email alerts
|

Does Natural Mentoring Matter? A Multilevel Meta‐analysis on the Association Between Natural Mentoring and Youth Outcomes

Abstract: In this meta‐analytic review, we examined the relation between natural mentoring and youth outcomes in four domains: academic and vocational functioning, social‐emotional development, physical health, and psychosocial problems. Natural mentoring relationships are thought to foster positive youth development and buffer against the risks associated with the tumultuous years of adolescence. Two separate meta‐analyses were conducted on the presence of a natural mentor and the quality of the natural mentoring relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
129
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 98 publications
6
129
1
2
Order By: Relevance
“…Additionally, as the compassionate presence of the mentor and relatedness emerge to be significant association extents impacting constructive youth improvement, the mentor-mentee connection may also be examined from the standpoint of attachment theory (Van Dam et al 2018). Numerous research studies propose that several factors, such as rate of recurrence or constancy of relationship between mentors-mentees or point of continuing programme support, may affect youths' and mentors' discernments of associational worth or counterpart coordination (Martin & Sifers, 2012;Larose et al, 2015;Zhou et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, as the compassionate presence of the mentor and relatedness emerge to be significant association extents impacting constructive youth improvement, the mentor-mentee connection may also be examined from the standpoint of attachment theory (Van Dam et al 2018). Numerous research studies propose that several factors, such as rate of recurrence or constancy of relationship between mentors-mentees or point of continuing programme support, may affect youths' and mentors' discernments of associational worth or counterpart coordination (Martin & Sifers, 2012;Larose et al, 2015;Zhou et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Opportunities for youth engagement in prosocial activities with adults in supportive environments are also critical to behavioral health, as well as protective against risky behaviors (e.g., alcohol and other drug use, involvement in delinquent behaviors) (Miranda‐Chan, Fruiht, Dubon, & Wray‐Lake, ; Reynolds & Parrish, ; Van Dam et al., ). In addition to the influence of parents, the supportive role of “other” adults, sometimes referred to as non‐parental adults, significantly contributes to young people's growth and development (DuBois & Silverthorn, ; Fruiht & Chan, ; Hurd, Tan, & Loeb, ; Raposa, Dietz, & Rhodes, ; Sánchez, Hurd, Neblett, & Vaclavik, ; Sánchez, Mroczkowski et al., ; Schwartz & Rhodes, ), despite their risk status (Van Dam et al., ). Non‐parental adults are teachers, coaches, clergy, neighbors, or extended family through whom youth gain guidance, social support, role modeling, opportunities for skill building, and advocacy.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐parental adults are teachers, coaches, clergy, neighbors, or extended family through whom youth gain guidance, social support, role modeling, opportunities for skill building, and advocacy. Extant literature demonstrates the importance of non‐parental adult support across developmental contexts, including the family, religious organizations, schools, and neighborhood involvements, (Hagler, ; Van Dam et al., ). With the growth of neighborhood effects research highlighting the importance of neighborhood context on youth outcomes (Bolland & McCallum, ; Dupéré, Leventhal, & Vitaro, ; Raposa, Erickson, Hagler, & Rhodes, ), there is a need for better understanding of the role of neighborhood non‐parental adults where youth reside.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multilevel meta‐analysis on the association between natural mentoring and youth outcomes showed a positive association, with social–emotional and academic and vocational functioning benefitting the most (Van Dam et al, ). Results also showed that regardless of risk status (including youth in foster care), natural mentoring was beneficial.…”
Section: Introductionmentioning
confidence: 99%